Pediatric oncology services in Colombia - Amaranto Suarez Mattos (Colombia Médica, 2018)
Methods: descriptive study of secondary source, the Special Register of Health Providers of the Ministry of Health and Social Protection was consulted, in order to identify the institutions that had enabled hospitalization services of medium or high complexity, chemotherapy, specialized consultation, emergencies, oncological surgery, and radiotherapy or nuclear medicine. The information is reported in absolute frequencies.Results: Seventy one institutions have hematology-oncology consultation, 39 institutions have chemotherapy and hospitalization services of medium or high complexity, and 18 have radiotherapy enabled. Only nine of the institutions include all the services that are necessary for comprehensive care.Conclusion: Colombia has a sufficient supply of services for the care of children with cancer. Only a minority are in institutions that have the capacity to guarantee the integrality of the attention.